A Novel Robust Mesh Watermarking Based on BNBW. (13th March 2011) - Chen Chen, Liping Liping; Kong Kong, Xiangzeng Xiangzeng; Weng Weng, Bin Bin; Yao Yao, Zhiqiang Zhiqiang; Pan Pan, Rijing Rijing
Abstract : As a solution to copyright protection of the digital media, digital watermarking techniques have been developed for embedding specific information to identify the owner in the host data imperceptibly. Nowadays, most watermarking methods mainly focused on digital media such as images, video, audio, and text, and very few watermarking methods have been presented for 3D models relatively. In the paper, a new robust watermarking scheme is presented which is based on biorthogonal nonuniform B-spline wavelets (BNBW) in the frequency domain for the purpose of copyright protection in the area of CAD, CAM, CAE, and CG. The watermark is embedded by modulating the wavelet coefficient vectors with the watermark in the frequency domain. The relative experiments prove that this approach not only can withstand common attacks on 3D models such as polygon mesh simplifications, addition of random noise, model cropping, translation, rotation, scaling, as well as a combination of such attacks but also can detect and locate tampered vertices.